A Decorporealized Theory? Considerations About Luhmann’s Conception of the Body - Calise, Santiago Gabriel (Pandaemonium Germanicum, 2015)
The aim of this paper is to analyze the concept of body developed by Luhmann's systems theory. Privileged places where one can look for the body will be the interpenetration between human beings and the concept of socialization. Another fundamental problem is the relationship between semantics and body, although the most explicit presence of the body in this theory comes with the concept of symbiotic mechanisms or symbols. The last place where this enquiry will look for a bodily reference are emotions, which were highly ignored by Luhmann. Alternative approaches explored in the paper are treating the body as a structure, as a medium or as an internal environment.